When you are born matters: The impact of date of birth on educational outcomes in England - Claire Crawford; Lorraine Dearden; Costas Meghir (Institute for Fiscal Studies (IFS), 2010)
This paper examines the impact of month of birth on national achievement test scores in England whilst children are in school, and on subsequent further and higher education participation. Using geographical variation in school admissions policies, we are able to split this difference into an age of starting school or length of schooling effect, and an age of sitting the test effect. We find that the month in which you are born matters for test scores at ages 7, 11, 14 and 16, with younger children performing significantly worse, on average, than their older peers. Furthermore, almost all of this difference is due to the fact that younger children sit exams up to one year earlier than older cohort members. The difference in test scores at age 16 potentially affects the number of pupils who stay on beyond compulsory schooling, with predictable labour market consequences. Indeed, we find that the impact of month of birth persists into higher education (college) decisions, with age 19/20 participation declining monotonically with month of birth. The fact that being young in your school year affects outcomes after the completion of compulsory schooling points to the need for urgent policy reform, to ensure that future cohorts of children are not adversely affected by the month of birth lottery inherent in the English education system.
Keywords: I21; I28; 330; Economics of Education; Month of Birth; Educational Outcomes; Altersgruppe; Schüler; Kognition; Bildungsniveau; England